NIIF para PYMES sección 13 y su influencia en la Presentación de los Estados Financieros en la empresa Proveedora de Insumos Médicos PIM, Riobamba período 2022. - Colcha Colcha, Amanda Mishel (2025)
This research aims to perform an accounting evaluation of the changes and variations, applying the IFRS for SMEs section 13 in the company Proveedora de Insumos Médicos PIM, period 2022. For this purpose, it was convenient to use a non-experimental design, allowing an evaluation of the facts that occurred without manipulating the variables; complementarily, the qualitative approach contributed to the deep understanding of the observed phenomena based on the data collection and their interpretative analysis, the use of techniques and instruments such as the interview and direct observation contributed to obtaining relevant data, It was identified that the application of section 13 of the IFRS for SMEs has a significant impact on the financial statements, since the valuation of inventories influences the determination of the cost of sales and therefore, on the gross and net profit, by making changes in the valuation or recognition of the inventory affects the financial structure. In contrast, an undervalued inventory underestimates the operating capacity, concluding that the company did not calculate the impairment of inventories. This generated a surplus in the inventory, increasing the value of the assets and, therefore, the results of the statements of financial position. This process allowed the identification of variations and the application of adjustments that led to a transparent representation of assets. The aforementioned recommendations allowed the implementation of an integral inventory control system that allows the company to follow up on the variations and changes in the inventory in real-time, considering that the company manages high inventory volumes.